2021
DOI: 10.1002/ceat.202000470
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Zinc Oxide Nanoparticles by Justicia adhatoda Leaves and Their Antimicrobial Activity

Abstract: Zinc oxide is recognized as one of the best antimicrobial agents. Zinc oxide nanoparticles were fabricated through a green approach using zinc sulfate, zinc nitrate, and zinc acetate dihydrate as precursors and an extract of Justicia adhatoda leaves as a reducing agent. The synthesized zinc oxide nanoparticles were checked for their antimicrobial activity against the bacterial strains Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and the fungal strains Aspergillus niger, Aspergillus flavus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The ZnO-NPs synthesized from the extracts of Rosa indica , Justicia adhatoda , Vitex negundo , Mentha pulegium , and Cassia fistula were reported to inhibit the growth of broad-spectrum pathogens [ 16 , 17 , 18 , 19 , 20 ]. Currently, plant-mediated synthesized nanoparticles are observed to possess photocatalytic activity [ 15 , 20 , 21 , 22 ] and they have shown more effective results than chemically prepared nanoparticles [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ZnO-NPs synthesized from the extracts of Rosa indica , Justicia adhatoda , Vitex negundo , Mentha pulegium , and Cassia fistula were reported to inhibit the growth of broad-spectrum pathogens [ 16 , 17 , 18 , 19 , 20 ]. Currently, plant-mediated synthesized nanoparticles are observed to possess photocatalytic activity [ 15 , 20 , 21 , 22 ] and they have shown more effective results than chemically prepared nanoparticles [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis sativa was utilised as a reducing and stabilising agent in this work, and zinc sulphate was used as a precursor. The synthesis of CNS-ZnONPs is thought to be triggered by aqueous leaf extract's reducing enzymes and capping agents, such as secondary metabolites, which work together to decrease zinc sulphate 14 . UV-VIS spectra indicated the synthesis of CNS-ZnONPs, and TEM confirmed the particle size distribution profile of the synthesised CNS-ZnONPs.…”
Section: Discussionmentioning
confidence: 99%
“…The various article demonstrated that synthesized ZnONPs form the green routes extracts obtained from diverse plants which produce NPs of different sizes and shapes. ZnONPs have different shapes like nanoflowers, nanosphere, hollow sphere, hexagonal wurtzite, and nanorods were described by Pachaiappan et al, [12][13][14] . While ZnO is hydrophilic, hydrophobic films are effective in preventing biofilm adherence.…”
Section: Introductionmentioning
confidence: 98%
“…& Schult. Diuretic, emmenagogue and purgative Ag Antibacterial [ 128 ] Justicia adhatoda L. Antiinflammatory, antipyretic ZnO Antimicrobial [ 129 ] Lantana camara L. Antimicrobial Ag Antioxidant, anticancer and antimicrobial [ 127 , 130 ] Laurus nobilis L. Antiseptic, antioxidant, digestive and anticancer ZnO Anticancer and antibacterial [ 131 ] Lavandula stoechas L. Antibacterial, anticholinesterase inhibition and antioxidant Ag Antibacterial, antioxidant [ 132 ] Matricaria chamomilla L. Antifungal, anti-inflammatory, antimicrobial and antioxidant Ag Anticancer [ 133 ] Antimicrobial [ 134 ] CuO Antioxidant and DNA cleavage [ 135 ] M. pulegium Carminative, antitussive, antimicrobial, antioxidant and antiseptic effects Ag Antimicrobial and anticancer [ 80 ] Fe None tested [ 136 ] Morinda citrifolia L. Anticancer, analgesic, antimicrobial, and antiinflammatory activity …”
Section: Medicinal Plants and Metals In Green Synthesis Of Nanoparticlesmentioning
confidence: 99%